2013
DOI: 10.1007/s00204-013-1146-x
|View full text |Cite
|
Sign up to set email alerts
|

Differential methylation of the arsenic (III) methyltransferase promoter according to arsenic exposure

Abstract: Inorganic arsenic is methylated in the body by arsenic (III) methyltransferase. Arsenic methylation is thought to play a role in arsenic-related epigenetic phenomena including aberrant DNA and histone methylation. However, it is unclear whether the promoter of the AS3MT gene, which codes for arsenic (III) methyltransferase, is differentially methylated as a function of arsenic exposure. In this study we evaluated AS3MT promoter methylation according to exposure, assessed by urinary arsenic excretion in a strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 63 publications
0
18
1
Order By: Relevance
“…The probes identified in the present study were compared against the cell population-related list identified by Kile et al (2014) in order to test whether the iAs-associated changes were related to potential shifts in cell population. Additionally, the probes/ genes identified in the present study were also compared with probes/genes previously identified in other human studies as having DNA methylation changes associated with iAs exposure (Chanda et al, 2006;Gribble et al, 2014;Koestler et al, 2013;Marsit et al, 2006;Smeester et al, 2011).…”
Section: Methodsmentioning
confidence: 94%
“…The probes identified in the present study were compared against the cell population-related list identified by Kile et al (2014) in order to test whether the iAs-associated changes were related to potential shifts in cell population. Additionally, the probes/ genes identified in the present study were also compared with probes/genes previously identified in other human studies as having DNA methylation changes associated with iAs exposure (Chanda et al, 2006;Gribble et al, 2014;Koestler et al, 2013;Marsit et al, 2006;Smeester et al, 2011).…”
Section: Methodsmentioning
confidence: 94%
“…We also cannot discount the possibility that in addition to the strong LD, the genotype at one variant/gene can affect the expression at another. In fact, AS3MT variants may matter for gene expression in the SHS (Gribble et al 2014). Additional mechanistic and epidemiological research is needed to confirm the relevance of GSTO and other functional variants in arsenic metabolism and toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Based on linear regression analysis a hypomethylated region in the AS3MT promoter was associated with higher arsenic exposure. These results suggest that not only the gene polymorphism but also the promoter regulation is disrupted by arsenic [59]. These studies clearly suggest that governance of arsenic metabolism may be playing a very important role that could provide indications on the level of toxicity arsenic would induce on prolonged exposure.…”
Section: Methyltransferasesmentioning
confidence: 74%
“…The MMA% increased uniformly according to the number of alleles for each SNP (mean MMA% was 7.5% for GG, 8.8% for GT, and 9.7% for TT carriers). Recently, Gribble et al [59] evaluated methylation status of 48 CpG loci at the AS3MT promoter region from 48 participants. Based on linear regression analysis a hypomethylated region in the AS3MT promoter was associated with higher arsenic exposure.…”
Section: Methyltransferasesmentioning
confidence: 99%